Management of Breast and Nipple Problems in Breastfeeding Mothers: Systematic Review: Management of Breast and Nipple Problems in Breastfeeding Mothers - safitriana, safitriana; Budiati, Tri; Rachmawati, Imami Nur (Universitas Ahmad Dahlan, 2024)
Introduction: Problems in the breasts and nipple are commonly faced by mothers which affects breastfeeding process. Appropriate and suitable intervention for breast and nipple problems that occur is one of the competencies both health workers and mothers must know Objective: To identify and explain breast and nipple problems that occur in breastfeeding mothers. 6 electronic databases were used; Science Direct, ProQuest, Springer Link, Taylor & Francis Online, Clinical Key Nursing, and Google Scholar. Results: There were 12 articles (sample 1,980) with breast and nipple problems in breastfeeding mothers there are breast engorgement (65%), breast pain (52.5%), plugged milk ducts (45.9%), nipple pain (15.5%), mastitis (10.5%), cracks and lesions on the nipple (9.7%), inverted nipple (4.2%), and breast abscess (0.6%). Five Steps Systematic Therapy (FSST) intervention can overcome breast pain, breast engorgement, mastitis, plugged milk ducts. Low-Level Laser Therapy can treat pain, cracks and nipple lesions. Reverse pressure softening technique can treat breast engorgement. Therapeutic breast massage can treat breast pain, breast engorgement, plugged milk ducts. Integrated Breast Massage can treat plugged milk ducts. Hoffman exercise and inverted syringe can correct inverted. Ultrasound-guided percutaneous catheters and hydrostatic pressure irrigation can treat breast abscesses. Lanolin, breast milk, aloe vera and olive oil were effective in treating pain, cracks and nipple lesions; Cold cabbage can treat breast pain and breast swelling. Conclusion: Breast and nipple problems in breastfeeding mothers can be addressed with all interventions.